Adsorption of Cu (II) and Zn (II) onto activated carbon derived from breadfruit (Artocarpus atilis) pericarp - Joshua P. Biscocho. 4 0 16; 5 (2017)
u
Undergraduate Thesis: (Bachelor of Science in Chemistry) - Pamantasan ng Lungsod ng Maynila, 2017.
Keywords: 2 -- 0; 6; 20; 20; 2